1986
DOI: 10.3102/00028312023003460
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Judgments About Their Students: The Effect of Cognitive Simplification Strategies on the Rating Process

Abstract: The common practice of asking teachers to provide ratings of their students is based on questionable assumptions about the ability of teachers to accurately integrate information from their numerous encounters with students. Borrowing from research in social cognition, an information-processing model of the rating process was proposed and tested by asking 18 teachers to rate 16 hypothetical student profiles formed by systematically varying information along six different dimensions. The results suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Although the effect sizes for both Reading and Mathematics were small, teachers tended to rate more reliably those with extended learning support placement. These findings are also consistent with the outcome of studies by Cadwell and Jenkins (1986) and Carr and Kurtzcostes (1994). Cadwell and Jenkins (1986) reported that teacher ratings of students' academic performance were reliable with longer placement in learning support.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the effect sizes for both Reading and Mathematics were small, teachers tended to rate more reliably those with extended learning support placement. These findings are also consistent with the outcome of studies by Cadwell and Jenkins (1986) and Carr and Kurtzcostes (1994). Cadwell and Jenkins (1986) reported that teacher ratings of students' academic performance were reliable with longer placement in learning support.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are also consistent with the outcome of studies by Cadwell and Jenkins (1986) and Carr and Kurtzcostes (1994). Cadwell and Jenkins (1986) reported that teacher ratings of students' academic performance were reliable with longer placement in learning support. One possible explanation is that the teacher judgements improve as they got to know their students' learning behaviours better.…”
Section: Discussionsupporting
confidence: 92%
“…This type of assessment should occur in a naturalistic setting (Williams et al 2003) and requires that a rater observing an examinee's clinical encounter with a patient, (1) acquires information about that examinee's abilities, (2) synthesizes the data they gather from the performance, and (3) interprets the data so as to make a decision (judgment-rating) (Kishor 1994;Landy and Farr 1980;Tweed and Ingham 2009). Since raters are, in essence, the measuring instruments of PBA (Cadwell and Jenkins 1986) it is necessary to further our understanding of how they accomplish the complex task of assessing examinees' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars in this field, borrowing from research in social cognition, propose information-processing models of the rating process. In an interesting introduction to their own work, Cadwell and Jenkins (1986) suggest that when raters are asked to complete a behavioural rating scale, they retrieve from their memory a cognitive representation of the individual to be rated. This representation is formed and modified through repeated observations and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…More recent research has tended to support Schaffer's conclusions and expand them in the line of implicit theories governing rating processes. Cadwell and Jenkins (1986) illustrate that teachers' ratings are interconnected by an implicit theory of student behaviour largely based on two dimensions: academic items (persistence on tasks until completion, not being distracted) vs. non-academic items (tendency to positively react to new stimuli, easily modifying behaviour in response to routine changes). A further result is that if students are described as "good readers" or "good-in-maths'' or "obedient", they are better rated in perseverance at schoolwork and as quiet boys or girls (the authors did not manipulate the students' gender).…”
Section: Introductionmentioning
confidence: 99%